The importance of surveying in determining denture design in partially removable - Armawati Arafi; Ike D. Habar (DiscoverSys Inc., 2017)
Objective: The purpose of making partially removable dentures is for the rehabilitation of tooth loss situations, mastication, esthetics and improving the health of the oral tissues. Some patients are dissatisfied with removable denture primarily at the time of functioning, the denture becomes unstable, so clinicians are expected to understand how to maximize every opportunity to provide and stabilize artificial denture by using surveyors.Methods: The references in this review are taken from textbook and internet search using Google with key words was carried out. Full text articles in English that were published from 1981 to 2014 are presented. In this review explains about surveying in prosthodontics. Surveyor is a tool for alignment used in making artificial teeth to find and describe the contours and positions of abutment teeth and related structural structures. The goal is to analyze the model for the best path of insertion selection.Results: A fundamental requirement in understanding the use of surveyors is to prevent the inappropriateness of path of insertion. To get a good guide plane should be done surveying. This guide plane is one of the important factors in determining the path of insertion and the stability of partially removable denture.Conclusion: The dentist should precisely control the use of surveyors in the manufacture of partially removable dentures. Thus it will produce a stable denture and can support the mastication function.